India Development Update, October 2014 - World Bank Group (Washington, DC, 2014)
Growth rebounded significantly due to strong industrial recovery aided by growth in investment and exports. Capital flows are back, signaling growing investor confidence, as inflation has moderated from double digits, exchange rate has stabilized, and financial sector stress has plateaued. Monetary policy continuity has been maintained and there has been some progress on fiscal consolidation. With the economy still below potential and reform momentum picking up, growth is expected to strengthen over the medium-term. Inflation is expected to decline with monetary policy switching to inflation targeting while the current account deficit is expected to widen somewhat as import demand and capital inflows rise. Fiscal consolidation is expected to continue through stronger revenue mobilization. Downside domestic risks can be offset through accelerated structural reforms.